Modelling Financial Contagion in the South African Equity Markets Following the Subprime Crisis - Niyitegeka, Olivier; Tewari, Dev D. (Journal of Economics and Behavioral Studies, 2019)
This paper used wavelet analysis and Dynamic Conditional Correlations model derived from the Multivariate Autoregressive Conditional Heteroskedasticity (MGARCH-DCC) to investigate the possible presence of financial contagion in the South African equity market in the wake of the subprime crisis that occurred in the United States. The study uses Dornbusch, Park and Claessens’s (2000) broader definition which asserts that financial contagion only takes place if cross-correlation between two markets is relatively low during the tranquil period, and that a crisis in one market results in a substantial increase cross-market correlation. Using wavelet analysis, the study found high levels of correlation during the subprime financial crisis in both smaller and longer timescales. In the former, high correlation was identified as financial contagion, whereas in the latter it was found to indicate co-movement due to financial fundamentals. The high correlation was identified for small scales 3, 4 and 5 that range from a week to one month indicates the presence of contagion. The study also used the MGARCH-DCC model to compare the cross-market correlation between the SA and the US markets, during a ‘pre-crisis’ and ‘crisis’ period. The study used data for the period between January 2005 and December 2007 for the ‘pre-crisis’ period and that for the period from January 2008 to December 2014 for the ‘crisis’ period. The results indicate cross-market linkages only during the crisis period; hence, it was concluded that cross-market correlation during the period of financial turmoil in the US was the result of financial contagion.